Level of knowledge of primary mainstream and special needs educators in supporting inclusive transitions - Lyn, Joanna Mah Tjun; Loh, Sau Cheong; Rosli, Noor Aishah (Jurnal Pendidikan Bitara UPSI, 2020)
This study examines the level of knowledge of mainstream educators and special needs educators towards supporting inclusive transitions into Malaysian primary schools. The study identifies three stages important towards inclusive transitions, namely Pre-Transition Stage, During Transition Stage, and Post-Transition Stage. The study was conducted on both mainstream and special needs educators in primary schools (n = 608) across West and East Malaysia and a 5-point Likert scale questionnaire was constructed as well as disseminated to the educators. Findings were aggregated, scored, grouped and analysed in percentages according to low, moderate and high levels of knowledge. The results of the analysis demonstrated that there is a general lack of knowledge in both mainstream and special needs educators, and this is indicatory that both groups of educators are clearly not proficient, skilled or experienced enough to support transitions into mainstream classrooms. In addition, the analysis demonstrated, in all three levels of transition, that the special needs educators were marginally more knowledgeable in their roles and responsibilities in supporting students with special needs than the mainstream educators, as the special needs educators demonstrated moderate levels of knowledge respectively in the Post-transition stage (47.85), During transition stage (56.44) and Post-transition stage (74.23) while mainstream educators reportedly considered themselves as having low levels of knowledge throughout the entire inclusive transition in all 3 stages (55.32, 70.21, 50.35). The findings provide us with evidence needed to support previous claims by professionals for the need of more trained professionals, and shed some light on possible relations between the limited readiness of the Malaysian education system in resources towards embracing inclusion, and how the lack of training coupled with underwhelming sense of proficient knowledge may possibly correlate to the attitudes of the educators in inclusion.